Prevalence and Factor Associated with Severity of Dysmenorrhea Among Female Adolescent in Surakarta - Wrisnijati, Dita; Wiboworini, Budiyanti; Sugiarto, Sugiarto (Jurnal Gizi dan Pangan Soedirman, 2019)
ABSTRACT Dysmenorrhea is the most common health problem among female adolescent in Indonesia. Generally, dysmenorrhea decreases the quality of life due to negatively impact on every aspects. This study aim to investigate the prevalence and associated factors with severity of dysmenorrhea among female adolescent aged 15-17 years in Surakarta. This cross-sectional study design conducted among 274 female adolescent aged 15-17 years in State Senior High School 7 Surakarta. The samples selected by stratified random sampling technique. Data were analyzed using chi-square and binary logistic regression test. The results of this study showed the prevalence of dysmenorrhea among female adolescent aged 15-17 years was 89.8%. Several factors such as age of menarche (p<0.001; OR=0.08; 95% CI: 0.03-0.18), menstrual duration (p<0.001; OR=7.54; 95% CI: 3.37-16.86), pain onset (p=0.004; OR=3.34; 95% CI: 1.48-7.51), and pain duration (p<0.001; OR=3.96; 95% CI: 2.07-7.51) were found significantly associated with increased severity of dysmenorrhea. Meanwhile, family history of dysmenorrhea (p=0.296), menstrual cycle interval, and caffeine intake were not significantly associated. This study concluded that a high prevalence of dysmenorrhea among female adolescent aged 15-17 years in Surakarta was detected, and factor associated with its severity were age of menarche, menstrual duration, pain onset, and pain duration. Keywords : Primary dysmenorrhea, menstruation, pain, prevalence